2018
DOI: 10.1182/bloodadvances.2018016451
|View full text |Cite
|
Sign up to set email alerts
|

Rapid immune reconstitution of SCID-X1 canines after G-CSF/AMD3100 mobilization and in vivo gene therapy

Abstract: Key Points• IV delivery of FV vector using the phosphoglycerate kinase promoter outperforms EF1a-containing vector in the canine SCID-X1 model.• G-CSF/AMD3100 mobilization before in vivo FV vector delivery improves kinetics and clonal diversity of lymphocyte reconstitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 58 publications
3
37
1
Order By: Relevance
“…18 Preclinical studies have highlighted that reconstitution of functional B cells can be achieved if a preconditioning regimen is combined with gene therapy. 28,29 Our results show that busulfan facilitates durable engraftment of gene-corrected hematopoietic stem cells, allowing for long-term replenishment of all affected lymphocyte lineages in infants with newly diagnosed SCID-X1. 18,30 The use of pharmacokinetic-guided administration of busulfan ensured consistent drug exposure, which is especially critical in infants and young children -a patient population in which metabolism and clearance of busulfan vary considerably.…”
Section: Discussionmentioning
confidence: 72%
“…18 Preclinical studies have highlighted that reconstitution of functional B cells can be achieved if a preconditioning regimen is combined with gene therapy. 28,29 Our results show that busulfan facilitates durable engraftment of gene-corrected hematopoietic stem cells, allowing for long-term replenishment of all affected lymphocyte lineages in infants with newly diagnosed SCID-X1. 18,30 The use of pharmacokinetic-guided administration of busulfan ensured consistent drug exposure, which is especially critical in infants and young children -a patient population in which metabolism and clearance of busulfan vary considerably.…”
Section: Discussionmentioning
confidence: 72%
“…In regard to off target viral integrations, two such sites were recorded: one in the gut, another (potential) at the virus infusion site and none in the germ cells. An improved protocol was later implemented from the same group that included stem cell mobilization with G-CSF/AMD3100 prior to FV vector delivery and the substitution of the EF1a promoter with that of the pgk gene in the FV vector [59]. The data argue for the faster recovery of T cell numbers and a broad TcR repertoire, and are clinically relevant when considering the overall survival that climbed to 2.5 years as compared to 330 days in the previous study.…”
Section: Large Animal Preclinical Modelsmentioning
confidence: 98%
“…FV vectors have also been used for the genetic correction of the Wiskott-Aldrich syndrome (WAS) mouse model [58]. WAS is an X-linked disorder characterized by eczema, immunodeficiency, and micro-thrombocytopenia resulting in bleeding tendency [59]. Uchiyama et al, used a WAS cDNA under the control of two different promoters (an endogenous and an A2UOCE-derived 631 bp fragment) and demonstrated the correction of the WAS phenotypic disorders.…”
Section: Therapeutic Gene Transfer In Murine Preclinical Modelsmentioning
confidence: 99%
“…Transfer of therapeutic genes into long-term repopulating HSPCs can potentially cure blood disorders such as hemoglobinopathies and primary immunodeficiencies. Specifically, with regards to X-linked severe combined immunodeficiency (SCID-X1), recent data showed that this approach could be curative in animal models [7,8] together with very promising clinical results using gene therapy in SCID-X1 patients [1,9]. Despite these advances, gene therapy continues to face a number of challenges which, if not resolved, could be detrimental to the clinical translation of these approaches [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, our laboratory has optimized parameters for efficient transduction of human and canine CD34+ HSPCs by FVVs [31][32][33]. In the last decade, our group has demonstrated efficacy of FVV in correction of monogenetic diseases of hematopoietic origin in large animal models (non-human primates and canine) and has established the safety of FVV in-vivo [7,8,34,35]. In these pre-clinical studies, FVV-mediated transgene delivery maintained high and persistent levels of marker-gene expression possibly due to improved transduction of quiescent cells and to the novel envelope/receptor system used for stem cell entry [7,8].…”
Section: Introductionmentioning
confidence: 99%